Someone help me!!!Who is correct? Explain your reasoning.

Alejandra:


2a2b(−2ab3)−2 = (2a2b)(−2ab3)2

= (2a2b)(−2)2a2(b3)2

= (2a2b)22a2b6

= 8a4b7


Kyle:


2a2b(−2ab3)−2=2a2b(−2)−2a(b3)−2

= 2a2b(4ab−6)

= 2a2bb64a

= ab72

Respuesta :

Without the use of appropriate symbols and parentheses, it is hard to tell what the problem is. We think you might be trying to simplify
  2·a²b·(-2·ab³)⁻²
  = 2·(-2)⁻²·a²·a⁻²·b·b⁻⁶
  = 2/(4b⁵)
  = 1/(2b⁵)

If so, this would mean neither Alejandra nor Kyle is correct.

_____
First of all, look at the constants. It appears you have a multiplier of 2 at the front, and a multipier of -2 inside parentheses that are raised to the -2 power. The product of these is 2^(1-2) = 1/2. If Kyle's answer is (ab^7)/2, then the constant is correct. As is, Kyle's answer looks like a·b^(72), which is clearly incorrrect.
ACCESS MORE